Potato marketing channels in mozambique: A survey of tete province potato farmers and traders - Sandramo, Paulino Bartolomeu; Edriss, Abdi-Khalil (Canadian Journal of Agriculture and Crops, 2025)
This study analyzes the potato marketing channels in Tete Province of Mozambique involving potato farmers and traders, to critically report the actual trend of potato marketing, by assessing mainly potato price spread and marketing channels of potato production and marketing, given that this province concentrates potato production in the country. In the province, the study primarily targeted the districts of Tsangano, Angonia, Moatize, and Tete town, focusing on farmers, who are the main suppliers of potatoes. Primary data were collected in February 2021 through a survey employing structured questionnaires administered to 453 farmers in Tsangano and Angónia, and 152 traders across ten potato markets located in Tsangano, Angónia, Moatize, and Tete town. A multistage sampling method was utilized to select the locations for data collection. Marketing margin equations were applied to identify potato marketing channels and assess the profitability of this activity. Therefore, the study identified five market channels. Hence, farmers received 100% of the consumers’ price when they sold directly to consumers, followed by 50.4% to retailers and 42.1% to wholesalers. The smallholder potato farmers attained good market prices since the breakeven price was found to be 7.6 MZM/kg, which was below the prevailing market price of 12.8 MZM/kg. This means potato farmers are not making losses under the prevailing market price; the business is profitable, and they are not exploited by potato traders. Policy recommendations that support channel 1 should be strengthened since it would assist farmers in marketing potatoes through economies of scale in Mozambique.